Advanced Accounting, An Organisational Approach (Book). - Moore, Carl L. (The Accounting Review, 1962)
Reviews the book "Advanced Accounting, an Organisational Approach," by Norton M. Bedford, Kenneth W. Perry and Arthur R. Wyatt.